The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1751-3928.2008.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Isotope Geochemistry of Active Submarine Hydrothermal Field at Suiyo Seamount, Izu-Bonin Arc, West Pacific Ocean

Abstract: This report presents mineralogical, geochemical and isotopic data on samples obtained using the Benthic Multi-coring System (BMS) to drill a submarine hydrothermal deposit developed in a caldera on the summit of the Suiyo Seamount in the Izu -Bonin Island Arc, south of Japan. This deposit is regarded as the fi rst example of Kuroko-type sulfi de mineralization on a volcano at the volcanic front of an island arc. The mineralization and hydrothermal alteration below the 300 × 150-m area of active venting was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…7p; Table 4) and is probably similar to clear smokers described in MOR-related vent sites (Bogdanov et al, 2006b). At Suiyo volcano, the chalcopyrite-rich chimneys of black and grey smokers are widespread (Watanabe and Kajimura, 1993;Ishibashi and Urabe, 1995;Marumo et al, 2008). The studied sample of black to grey chalcopyrite-pyrite smokers was presented by T. Urabe.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…7p; Table 4) and is probably similar to clear smokers described in MOR-related vent sites (Bogdanov et al, 2006b). At Suiyo volcano, the chalcopyrite-rich chimneys of black and grey smokers are widespread (Watanabe and Kajimura, 1993;Ishibashi and Urabe, 1995;Marumo et al, 2008). The studied sample of black to grey chalcopyrite-pyrite smokers was presented by T. Urabe.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Numerous mineralogical data on modern black and white smokers are scattered through a number of publications (e.g., Halbach and Pracejus, 1993;Marumo et al, 2008;Scott, 1997;Lein et al, 2003;Bogdanov et al, 2006;Rona, 2008;Fouquet et al, 2010;Berkenbosh et al, 2012). Little is published on the mineral peculiarities of chimneys from the ancient VMS deposits (Herrington et al 1998;Maslennikova and Maslennikov, 2007;Maslennikov et al, 2009Maslennikov et al, , 2013Revan et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Seven boreholes (called APSK01 to APSK07) were drilled on the seafloor using BMS in June 2001, and three boreholes (APSK08 to APSK10) were added in July 2002. The analysis of core samples obtained from the boreholes have indicated that there is an impermeable layer, which consists of clay and anhydrite, at 1–3 m depth below the seafloor, and that over 300°C hydrothermal fluids are trapped below the layer (Urabe et al, 2002; Marumo et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Marumo et al 2008). Although it may be difficult to penetrate the fluid reservoir even with the maximum capacity, drilling by the BMS is accessible to a region where various interactions are expected to be induced by mixing between the hydrothermal component and entrained seawater.…”
Section: Introductionmentioning
confidence: 99%